Ecological and toxicological features of the effect of stable cesium on striated muscle tissue (myocardium and skeletal muscles) of mammals - O. Yermishev (Regulatory Mechanisms in Biosystems, 2023)
Recently, the risks of radiation danger have significantly increased. This is connected with the start of a full-scale war against Ukraine and the seizure of the Zaporizhzhya NPP by the Russian Federation, which has the second most powerful arsenal of nuclear weapons in the world. The majority of studies devoted to the effect of radioactive radiation on the human body and animals absolutely do not take into account the ecotoxic effect of the carrier and a chemical element. At the same time, the body does not distinguish between radioactive and non-radioactive isotopes of chemical elements and interacts with them during exchange processes. The aim of the work was to study the influence of stable cesium on the microscopic structure of striated muscle tissue, both skeletal and cardiac ones. The results of our research revealed that intensive accumulation of cesium for 24 days occurred in all the examined organs and tissues. In fact, the most intensive accumulative process appeared to be in the heart by 214.9 times and by 695.3 times with skeletal muscles, with a simultaneous decrease in potassium content by 19.2% and 29.1%, respectively, compared to intact rats. We can talk about the presence of two mechanisms of action of cesium on tissues, including striated muscles: as an antagonist of potassium, which concerns the transport system of the latter and as a toxic element that initiates peroxide processes with subsequent modification of membranes and their potassium channels. Functional disturbances in the work of potassium channels of excitable tissues in the repolarization phase occur in the conditions of an increase in intracellular cesium in striated muscles. These disorders can proceed according to the type of acquired "potassium" channelopathies, which in the myocardium can manifest in the form of rhythm disorders, prolonged QT syndrome, etc. This leads to the appearance of significant violations of the histological structure of the examined tissues. Cesium has pronounced damaging effects on both skeletal and cardiac striated muscle tissue, with morphological changes in skeletal and cardiac striated muscle tissue being generally similar. Dystrophic changes in the nuclei and cytoplasm of cardiomyocytes and striated muscles, signs of impaired blood circulation in the microcirculatory channel with the formation of vascular wall edema, destruction of endothelial cells, various types of hemorrhages and lymphohistiocytic infiltration of the stroma of fibers are the consequences of the toxic effect of cesium on tissues. Thus, the results of changes in the histological structure of striated muscles under the action of cesium chloride obtained by us indicate a fairly high cytocidal activity of stable cesium.